Application of Choice Theory Reality Therapy Integration Using Expressive Arts Activities in Implementing Individual Counseling Sessions - M.Horsi, Siti Suraiyah; Jusoh, Ahmad Jazimin; M.Horsi, Nor Samsiyah; Mohd Selamin, Intan Suhaini; M.Horsi, Abd Haris (International Journal of Education, Information Technology, and Others, 2024)
This study explores the use of expressive art activities as a tool to help teachers experiencing stress, anxiety, and depression. It employs a qualitative approach with the case study method. The sample consists of four teachers from a district in the State of Selangor. Data were collected through interviews and document analysis. The data were then analyzed using the pattern-matching method, grouping the data into themes, subthemes, or categories with specific codes. The study's findings indicate that art activities in individual counseling sessions offer an alternative approach for counselors to provide services. Eleven themes emerged from the study: session implementation procedures, harmony in relationships, health status for survival, role adaptation, significant individual support, hope to remain enthusiastic, calmness under stress, personal values, expressive art activities that guide overall behavior, counselor skills, and integration modules that positively impact clients. The findings suggest that personal values influence clients' lifestyles in achieving their desired goals.